2012
DOI: 10.17161/iallt.v42i1.8503
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration through Wiki and Paper Compositions in Foreign Language Classes

Abstract: This study investigates the nature of collaboration on wikis as opposed tothe nature of collaboration resulting in a paper composition. In order tounderstand this phenomenon students were placed in groups of four andasked to write two essays during the semester. On one essay students wereasked to produce a composition in the target language on a wiki. Onanother they were asked to produce a composition that would be given tothe teacher in hard copy. Specific research questions includeddetermining to what extent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…The current body of research has moderately discussed students' revising behaviors in the wiki writing process (Arnold, Ducate, & Kost, 2012;Kessler & Bikowski, 2010;Mak & Coniam, 2008), the wiki writing product in terms of textual or metadiscourse features (Elola & Oskoz, 2010;Kuteeva, 2011), and student perceptions of wiki-based collaborative writing (Chao & Lo, 2009;Martinsen & Miller, 2012;Zorko, 2009). Yet, limited literature (Arnold et al, 2012;Bradley, Linstrom, & Rystedt, 2010;Li & Zhu, 2011) has delved into the nature and dynamics of small groups' interactions during wiki-mediated collaborative writing processes, and few have analyzed students' ongoing communication in the form of written discourse posted in the wiki "Discussion" which I believe can provide a great affordance for collaborative writing activities.…”
Section: Wiki-mediated Collaborative Writingmentioning
confidence: 99%
“…The current body of research has moderately discussed students' revising behaviors in the wiki writing process (Arnold, Ducate, & Kost, 2012;Kessler & Bikowski, 2010;Mak & Coniam, 2008), the wiki writing product in terms of textual or metadiscourse features (Elola & Oskoz, 2010;Kuteeva, 2011), and student perceptions of wiki-based collaborative writing (Chao & Lo, 2009;Martinsen & Miller, 2012;Zorko, 2009). Yet, limited literature (Arnold et al, 2012;Bradley, Linstrom, & Rystedt, 2010;Li & Zhu, 2011) has delved into the nature and dynamics of small groups' interactions during wiki-mediated collaborative writing processes, and few have analyzed students' ongoing communication in the form of written discourse posted in the wiki "Discussion" which I believe can provide a great affordance for collaborative writing activities.…”
Section: Wiki-mediated Collaborative Writingmentioning
confidence: 99%
“…Organized feedback from peers and instructors has also been shown to lead to more edits in participants' own writings than in their group members' texts (Arnold, Ducate, & Kost, 2012). The divergent findings further underline the value of task communication, which can occur face-to-face (Martinsen & Miller, 2012) or via computer-mediated communication (Elola & Oskoz, 2010;Yeh, 2014;Zheng, Niiya & Warschauer, 2015), and of learner training for peer editing to decrease apprehension when editing and to promote a deeper feeling of co-ownership of a produced text (Min, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…Computer-mediated group writing can easily be facilitated with tools such as a wikis (Arnold, Ducate, & Kost, 2012;Aydin & Yildiz, 2014;Elola & Oskoz, 2010;Kessler, 2009;Kessler & Bikowski, 2010) and online word processing (Kessler, Bikowski, & Boggs, 2012). Given technology's unique affordances for collaboration and writing, such writing might be fundamentally different from paper-based tasks, as supported by the findings of Martinsen and Miller (2012). As one of the few studies comparing group writing on wikis vs. paper, they found that wikis encouraged more true collaboration among beginning foreign language learners, whereas paper-based tasks encouraged more cooperation with students rarely reading each other's work before assembling it.…”
Section: Group Writingmentioning
confidence: 93%
“…In contrast to that, it was empirically proved that wikis can facilitate collaborative learning. Evidences can be observed in Awada and Diab (2018), Krasnova et al (2016), Li et al (2012), Martinsen and Miller (2012), Pellet (2012) and Yusoff et al (2012). This result contradicted most of these studies.…”
Section: What Is the Effect Of The Vocabulary Wiki On Students' Collamentioning
confidence: 91%